KEWENANGAN JAKSA MENGAJUKAN PENINJAUAN KEMBALI TERHADAP PUTUSAN YANG TELAH MEMPEROLEH KEKUATAN HUKUM TETAP DALAM SISTEM PERADILAN PIDANA - Rifdah Juniarti Hasmi; Erdianto Effendi; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Reconsideration is one of extraordinary law efforts, based Article 263 paragraph (1) Criminal Procedure Code states that only the convicted person or his heirs can submit a reconsideration. Fundamental philosophy of this states based on that country has miscarriage justice the civils who doesn’t to be sinful and can’t repaired by the ordinary law efforts. But, in criminal justice practices, remedy reconsideration may be filed by the public prosecutor. The purpose of this study, to determine the urgency of the committee reconsideration in Indonesia, to determine the meaning of fundamental philosofi in Article 263 Criminal Procedure Code to give emphasis that only the convicted person or his heirs can submit a reconsideration, to determine the Rights of the public prosecutor asking reconsideration the decision of the judge who already have permanent legal force in positive law’s Indonesia. This type of research is a normative legal research or can referred to as the doctrinal legal research. The results of this research is, The urgency of the committee reconsideration for enforced law to reach a justice for the convicted person or his heirs toward a decision of the judge who already have permanent legal as one of efforts can be able to endure by the convicted person or his heirs can submit a reconsideration, Article 263 paragraph (1) Criminal Procedure Code to give emphasis that only the convicted person or his heirs can submit a reconsideration as redeeming the contry sinful to the convict, the Rights of the public prosecutor asking reconsideration in positive law’s Indonesia there’s no a regulation about it and there’s no a prohibition to do that.Keywords : Reconsideration-Public Prosecutor-Criminal Justice System